Understanding Patient Perspectives of the Impact of Anemia in Chronic Kidney Disease: A United States Patient Survey. (April 2022) - Grandy, Susan; Palaka, Eirini; Guzman, Nicolas; Dunn, Alicia; Wittbrodt, Eric T.; Finkelstein, Fredric O.
Anemia in chronic kidney disease (CKD) is associated with reduced health-related quality of life and physical functioning. This study investigated knowledge and awareness of anemia in patients with CKD in the United States (US) through an online, quantitative survey administered to patients aged ≥18 years with self-reported CKD, with or without anemia. Of 446 patients included, 255 (57.2%) were diagnosed with anemia and 191 (42.8%) were in the non-anemia cohort. In patients with anemia, 71.0% were aware of the relationship between CKD and anemia versus 52.9% in the non-anemia cohort. In the anemia cohort, 46.3% of patients were aware of their hemoglobin level, versus 27.2% in the non-anemia cohort. Despite 67.4% of patients with anemia believing their condition was well/very well managed, only 50% reported being informed about different treatments without prompting healthcare providers. In the US, patients with anemia and CKD perceived that anemia had a negative impact on physical health and emotional wellbeing. Results emphasize a lack of disease awareness, suggesting patients would benefit from further education on anemia in CKD.